1988
DOI: 10.2307/1590957
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidia-Positive Rates of Avian Necropsy Accessions Determined by Examination of Auramine O-Stained Fecal Smears

Abstract: Fecal smears from 112 avian necropsy accessions representing 431 birds were stained with auramine O and examined for Cryptosporidium oocysts by fluorescence microscopy. Stained Cryptosporidium oocysts fluoresced bright yellow-green and were easily differentiated from extraneous material by their uniform small size (approx. 5 micron) and morphology. The rates of cryptosporidia-positive accessions were 27.3% (9/33) of broilers, 10% (3/30) of broiler breeders, and 5.9% (1/17) of layers. Further analyses of availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 18 publications
1
8
0
2
Order By: Relevance
“…In comparison with broilers, there are few studies concerning Cryptosporidium infection in layer chickens. Two previous studies showed the infection rates were 5.9% (1/17) and 36.8% (25/68) in the USA and Japan, respectively (Itakura et al, 1984;Ley et al, 1988). In the present study, a 10.6% (163/1542) infection rate was observed in layer chickens.…”
Section: Methodssupporting
confidence: 58%
See 1 more Smart Citation
“…In comparison with broilers, there are few studies concerning Cryptosporidium infection in layer chickens. Two previous studies showed the infection rates were 5.9% (1/17) and 36.8% (25/68) in the USA and Japan, respectively (Itakura et al, 1984;Ley et al, 1988). In the present study, a 10.6% (163/1542) infection rate was observed in layer chickens.…”
Section: Methodssupporting
confidence: 58%
“…In Pekin ducks, Cryptosporidium infection was found only in the age group of 11 to 50 days (Table 2). Ley et al, 1988;Snyder et al, 1988;Goodwin et al, 1996). In European countries such as Scotland and Greece, the infection rates in broilers were 18.7% (26/139) and 24.3% (17/70), respectively (Randall, 1982;Papadopoulou et al, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…Although there are intensive studies and huge amount of information about the cryptosporidiosis prevalence in chickens from Europe, united states, American Latin countries and Japan [9,10,11,12,13] , we found no previous studies on Cryptosporidium infections of chickens in Syria.…”
Section: Introductionmentioning
confidence: 81%
“…Serological evidence for Cryptosporidium infection was found in 88% (22/25) of tested chickens in Scotland (Tzipori and Campbell, 1981), 30% of chickens in the USA . Up to 27% of chickens excreted Cryptosporidium oocysts (Ley et al, 1988), and 6.4% of histology case accessions at one diagnostic laboratory had a microscopical diagnosis(es) of cryptosporidiosis (Table 2). In the latter survey, Cryptosporidium was the second most common histologically-diagnosed protozoal infection in chickens.…”
Section: Host Species and Incidencementioning
confidence: 99%
“…DIAGNOSIS Infections with Cryptosporidium are routinely diagnosed by histological and cytological methods. Although examination of paraffin-embedded, haematoxylinand eosin-stained sections of organs has been the diagnostic method of choice (Luna, 1988), differential visible-light stain of respiratory epithelium and exudate (Henriksen and Pohlenz, 1981;Garcia et al, 1983) or fluourescent light stain of faecal smears (Ley et al, 1988) can help rapidly identify the organisms in cytological preparations. In addition, Nomarsky differential interference microscopy is useful for rapid examination of fresh (wet) cytological preparations for the presence of oocysts (Current, 1985b;Current and Snyder, 1988).…”
Section: Ma Goodwinmentioning
confidence: 99%